The Role of Zebrafish and Laboratory Rodents in Schizophrenia Research - Langova, Veronika; Vales, Karel; Horka, Petra; Horacek, Jiri (Frontiers in Psychiatry, 2020)
Schizophrenia is a severe disorder characterised by positive, negative and cognitive symptoms, which are still not fully understood. The development of efficient antipsychotics requires animal models of a strong validity, therefore the aim of the article were to summarise the construct, face and predictive validity of schizophrenia models based on rodents and zebrafish, compare the advantages and disadvantages of these models, and proposes future directions in schizophrenia modelling and indicates when it is reasonable to combine these models. The advantages of rodent models stem primarily from the high homology between rodent and human physiology, neurochemistry, brain morphology and circuitry. The advantages of zebrafish models stem in the high fecundity, fast development and transparency of the embryo. Disadvantages of both models origin in behavioural repertoires not allowing specific symptoms to be modelled, even when the models are combined. Especially modelling the verbal component of certain positive, negative and cognitive symptoms is currently impossible.